Changes in fluxes of carbon dioxide and methane caused by fire in Siberian boreal forest with continuous permafrost - Köster, Egle; Köster, Kajar; Berninger, Frank; Prokushkin, Anatoly; Aaltonen, Heidi; Zhou, Xuan; Pumpanen, Jukka (Journal of Environmental Management, 2020)
Rising air temperatures and changes in precipitation patterns in boreal ecosystems are changing the fire occurrence regimes (intervals, severity, intensity, etc.). The main impacts of fires are reported to be changes in soil physical and chemical characteristics, vegetation stress, degradation of permafrost, and increased depth of the active layer. Changes in these characteristics influence the dynamics of carbon dioxide (CO2) and methane (CH4) fluxes. We have studied the changes in CO2 and CH4 fluxes from the soil in boreal forest areas in central Siberia underlain by continuous permafrost and the possible impacts of the aforementioned environmental factors on the emissions of these greenhouse gases. We have used a fire chronosequence of areas, with the last fire occurring 1, 23, 56, and more than 100 years ago. The soils in our study acted as a source of CO2. Emissions of CO2 were lowest at the most recently burned area and increased with forest age throughout the fire chronosequence. The CO2 flux was influenced by the pH of the top 5cm of the soil, the biomass of the birch (Betula) and alder (Duschekia) trees, and by the biomass of vascular plants in the ground vegetation. Soils were found to be a CH4 sink in all our study areas. The uptake of CH4 was highest in the most recently burned area (forest fire one year ago) and the lowest in the area burned 56 years ago, but the difference between fire chronosequence areas was not significant. According to the linear mixed effect model, none of the tested factors explained the CH4 flux. The results confirm that the impact of a forest fire on CO2 flux is long-lasting in Siberian boreal forests, continuing for more than 50 years, but the impact of forest fire on CH4 flux is minimal. Peer reviewed